Answer:
6x^3 - 2x^2 -11x +4
Step-by-step explanation:
(3x-4)(2x^2+2x-1)
Multiply 3x by the second term
3x* (2x^2+2x-1)
6x^3 +6x^2 -3x
Multiply -4 by the second term
-4*(2x^2+2x-1)
-8x^2 -8x+4
Add these together, lining up the terms
6x^3 +6x^2 -3x
-8x^2 -8x+4
----------------------------------
6x^3 - 2x^2 -11x +4
Answer:
I was unsure about the way your question was written so I solved for two equations: f(x)=14(5-x)*2 and f(x)=14(5-x)+2
Step-by-step explanation:
Answer:
a. ![\frac{2x + 3}{x+5}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%20%2B%203%7D%7Bx%2B5%7D)
b. x ≠ -5 (Vertical asymptote) and x ≠ 5 (Hole)
Step-by-step explanation:
Factor the numerator (Grouping):
Two numbers that multiply to -30 and add to -7 = -3 and 10
![[2x^2 - 10x] + [3x - 15]](https://tex.z-dn.net/?f=%5B2x%5E2%20-%2010x%5D%20%2B%20%5B3x%20-%2015%5D)
![(2x + 3)(x - 5)](https://tex.z-dn.net/?f=%282x%20%2B%203%29%28x%20-%205%29)
Factor the denominator (Difference of Two Squares):
= ![(x +5)(x-5)](https://tex.z-dn.net/?f=%28x%20%2B5%29%28x-5%29)
Factored Expression:
(x - 5) can be factored out of top and bottom as a hole-
![\frac{(2x + 3)(x - 5)}{(x + 5)(x - 5)} = \frac{2x + 3}{x+5}](https://tex.z-dn.net/?f=%5Cfrac%7B%282x%20%2B%203%29%28x%20-%205%29%7D%7B%28x%20%2B%205%29%28x%20-%205%29%7D%20%3D%20%5Cfrac%7B2x%20%2B%203%7D%7Bx%2B5%7D)
Variable Restrictions:
Denominator ≠ 0
![x + 5 = 0\\x = -5](https://tex.z-dn.net/?f=x%20%2B%205%20%3D%200%5C%5Cx%20%3D%20-5)
Vertical asymptote at x = -5 ⇒ x ≠ -5
Answer:
1
Step-by-step explanation:
A linear equation (degree 1) will have one root. A quadratic equation (degree 2) will have two roots. A cubic equation (degree 3) will have three roots. An nth degree polynomial equation will have n roots.
Answer:
14x^3+39x^2+18x+20
Step-by-step explanation: